Do Private Household Transfers to the Elderly Respond to Public Pension Benefits? Evidence from Rural China - Plamen Nikolov; Alan Adelman (Global Labor Organization (GLO), 2019)
Aging populations in developing countries have spurred the introduction of public pension programs to preserve the standard of living for the elderly. The often-overlooked mechanism of intergenerational transfers, however, can dampen these intended policy effects, as adult children who make income contributions to their parents could adjust their behavior in response to changes in their parents' income. Exploiting a unique policy intervention in China, we examine using a difference-in-difference-in-differences (DDD) approach how a new pension program impacts inter vivos transfers. We show that pension benefits lower the propensity of adult children to transfer income to elderly parents in the context of a large middle-income country, and we also estimate a small crowd-out effect. Taken together, these estimates fit the pattern of previous research in high-income countries, although our estimates of the crowd-out effect are significantly smaller than previous studies in both middle- and high-income countries.
Keywords: D64; O15; O16; J14; J22; H55; R2; 330; life cycle; retirement; pension; inter vivos transfers; middle-income countries; developing countries; China; crowd-out effect; aging